67.1k views
4 votes

(\sec\left(x\right))/(\cos\left(x\right))-(\sin\left(x\right))/(\csc\left(x\right)\cos^(2)\left(x\right))Use the basic identities to change the expression to one involving only sines and cosines. Then simplify to a basic trig function.

User Alistra
by
4.9k points

1 Answer

5 votes

Answer:

1

Explanation:

First, convert all the secants and cosecants to cosine and sine, respectively. Recall that
csc(x)=1/sin(x) and
sec(x)=1/cos(x).

Thus:


(sec(x))/(cos(x)) -(sin(x))/(csc(x)cos^2(x))


=((1)/(cos(x)) )/(cos(x)) -(sin(x))/((1)/(sin(x))cos^2(x) )

Let's do the first part first: (Recall how to divide fractions)


((1)/(cos(x)) )/(cos(x))=(1)/(cos(x)) \cdot (1)/(cos(x))=(1)/(cos^2(x))

For the second term:


(sin(x))/((cos^2(x))/(sin(x)) ) =(sin(x))/(1) \cdot(sin(x))/(cos^2(x))=(sin^2(x))/(cos^2(x))

So, all together: (same denominator; combine terms)


(1)/(cos^2(x))-(sin^2(x))/(cos^2(x))=(1-sin^2(x))/(cos^2(x))

Note the numerator; it can be derived from the Pythagorean Identity:


sin^2(x)+cos^2(x)=1; cos^2(x)=1-sin^2(x)

Thus, we can substitute the numerator:


(1-sin^2(x))/(cos^2(x))=(cos^2(x))/(cos^2(x))=1

Everything simplifies to 1.

User David Artmann
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.